Effect of external magnetic field on the coexistence of SC and AFM in iron based superconductors. (March 2017) - Goi, S.K.; Pradhan, B.; Behera, Srikanta; Parida, P.K.; Mishra, R.N.
Abstract: We have studied the interplay of antiferromagnetism and superconductivity in presence of an applied external magnetic field for the iron based superconductors. For the purpose we have proposed a model Hamiltonian and solved it self-consistently by using the Zubarev's technique of double time Green's function technique. The self-consistent gap equations are solved numerically and interpreted the gap values from the of density of states plots. Abstract : Highlights: A Hamiltonian for Fe based SCs with SC and AFM interactions is proposed in presence of an external magnetic field. Zubarev's technique of single particle double time Green's functions is used for calculations. The interplay of the gap parameters are studied. The gap values are observed through DOS plots and the effect of external magnetic field shows the Zeeman split.